2019
DOI: 10.5812/sdme.82679
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Happiness and Quality of Educational Services with Academic Burnout Among Students of Zahedan University of Medical Sciences, Iran

Abstract: Background: Paying attention to students' academic burnout and identifying the factors affecting it is one of the concerns of higher education authorities. Objectives: The purpose of this study was to investigate the effect of quality of educational services and happiness on students' academic burnout. Methods: In this descriptive-analytical study, 477 students of Zahedan University of Medical Sciences participated in the academic year 2017 -2018. The sampling method was stratified. Data were collected using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…The findings of this study indicated a direct significant association between happiness and being married among nursing students. However, two previous studies did not show a significant relationship between happiness and students' marital status [ 51 , 52 ]. Consistent with our findings, a previous study reported that happiness was higher in married individuals than in single individuals [ 53 ].…”
Section: Discussionmentioning
confidence: 94%
“…The findings of this study indicated a direct significant association between happiness and being married among nursing students. However, two previous studies did not show a significant relationship between happiness and students' marital status [ 51 , 52 ]. Consistent with our findings, a previous study reported that happiness was higher in married individuals than in single individuals [ 53 ].…”
Section: Discussionmentioning
confidence: 94%
“…Examining the state of fear of negative evaluation among nursing students in this study also showed that its average was 29.61, and in fact, 36.4% of people have an average level of this variable. During a study conducted by Mabrouk Mohammad et al in Egypt, the results showed that the level of fear of negative evaluation among the majority of students was at an average level (24); also, a study conducted by Mazhari and colleagues in Iran showed that 40.6 percent of students were suffering from social phobia (27).…”
Section: Discussionmentioning
confidence: 98%
“…The results of the present study indicate that there is a negative and signi cant relationship between clinical competence in all three areas and fear of negative evaluation. Mazhari and his colleagues' studies to investigate social phobia and its relationship with academic status among the students of Kerman University of Medical Sciences (Iran) showed that among the studied students, 40.6% were suffering from fear of negative evaluation, and students signi cantly They believed that their academic performance was lower than reality due to their fear of speaking in public (27). Fear of negative evaluation is one of the issues related to people's mental health, which has an impact on a person's performance and can play a role as a predictive factor in the acquisition of clinical competence in nursing students, but a study that shows the relationship between this variable and clinical competence in different populations, including students, was not found, and the present study is the rst study conducted in this eld; therefore, more research is needed in this eld for a deeper investigation.…”
Section: Discussionmentioning
confidence: 99%